Analysis of Corruption Prevention Forms and Policies in Goods and Services Procurement: E-Procurement as a Solution - Nova, Deta Helisa; M. Sobri, Kgs.; Nadjib, Abdul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Procurement of Goods and Services (PBJ) is a crucial component of governance that supports transparency, sustainable development, and poverty alleviation. However, the procurement process is highly vulnerable to illegal practices such as bribery, bid manipulation, collusion, nepotism, cronyism, and abuse of power by public officials. This article aims to analyze the forms of corruption, their impact on PBJ, and the policies that can be implemented to address these issues. The research employed a literature review, analyzing 60 selected articles from SCOPUS and SINTA databases. The analysis results show that corruption in PBJ includes bribery, bid manipulation, cartels, collusion, political involvement, abuse of power, favoritism, nepotism, cronyism, bid-rigging, clientelism, price markup, and manipulation of PBJ quality. These irregularities have detrimental effects on the economic, social, and political aspects, as well as causing direct losses to the state and government institutions. The analysis suggests anti-corruption policies such as strict regulations, e-procurement technology, and strengthening oversight institutions to prevent these issues. E-procurement is an effective solution to enhance transparency and reduce interactions that are susceptible to bribery. In conclusion, collaborative efforts involving regulation, technology, and independent oversight are essential to achieving a transparent, competitive, and corruption-free procurement process. This research is expected to contribute to more effective PBJ policy reforms.